Monetary Policy Rules and the U.S. Business Cycle : Evidence and Implications - Rabanal, Pau (IMF Working Papers; Working Paper ;, 2004)
This paper estimates Taylor-type interest rates for the United States allowing for both time and state dependence. It provides evidence that the coefficients of the Taylor rule change significantly over time, and that the behavior of the Federal Reserve over the cycle can be explained using a two-state switching regime model. During expansions, the Federal Reserve follows a rule that can be characterized as inflation targeting with a high degree of interest rate smoothing. During recessions, the Federal Reserve targets output growth and conducts policy in a more active manner. The implications of conducting this type of policy are analyzed in a small scale new Keynesian model.